Antimicrobial potential of Anacardium occidentale Lin. against oral pathogens (Research, Society and Development, 2020)
Anacardium occidentale L., popularly known as cashew tree, is a plant native to Brazil, distributed in several tropical regions of the world. The studies describe several medicinal uses of Anacardium occidentale L., highlighting the anti-inflammatory, antioxidant and antimicrobial properties. Its antimicrobial potential has been studied to achieve new treatment options for oral pathologies. Therefore, this study aimed to present a bibliometric study of the antimicrobial and antifungal properties of the trunk and leaves of the cashew tree against oral pathogens. The following databases were analyzed: PubMed, Google Scholar, SciELO and Science Direct, of which 19 articles published in the last 10 years were selected. Most of the tests showed positive antifungal potential and promising antimicrobial properties. The results provide important data and perspectives on the use of Anacardium occidentale that can contribute to the treatment of diseases that affect the oral cavity, such as caries, candidiasis and periapical infections.